How should PCNA be assessed? Total of stained cells or only the most intensely stained ones? - Kemp, Claudio; Alberti, Vânia Nosé; Lima, Geraldo Rodrigues de; Carvalho, Filomena Marino de (São Paulo Medical Journal, 1998)
OBJECTIVE: This study aimed to analyse whether a marker of proliferative activity (PCNA) could provide a prognosis of tumor evolution and to determine whether different interpretation criteria could alter the results. METHOD: The presence of PCNA in 59 patients of state II (T2 NO,1 MO) mammary carcinoma was determined. RESULT: Numerical proportions of total and intensely stained cells were established. These data were compared with anatomopathological parameters. A significant association between higher cyclin values and worse histological and nuclear grading was encountered, particularly in patients with a "negative axilla" using the PCNA index. Cyclin values were not significant in relation to any parameters when indices from the intensely stained cells were considered exclusively. CONCLUSION: Higher nuclear (NG3) and histological (HGIII) grading, associated with a high PCNA index (>50), distinguish high-risk patients, and it is more appropriate considering all the stained cells as representative of PCNA indices, thus reflecting tumor aggressiveness.